2021
DOI: 10.1016/j.ctrv.2021.102289
|View full text |Cite
|
Sign up to set email alerts
|

Advanced oesophago-gastric adenocarcinoma in older patients in the era of immunotherapy. A review of the literature

Abstract: Gastric (G) and gastro-esophageal junction (GEJ) adenocarcinomas are of the most common and deadly cancers worldwide and affect mainly patients over 70 years at diagnosis. Older age has been associated in gastric cancers with distal tumour location, well-differentiated adenocarcinoma and microsatellite instability and is not identified itself as an independent prognostic factor. As immune checkpoint inhibitors recently changed the landmark of advanced G and GEJ adenocarcinomas treatment, we decided to perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 133 publications
1
6
0
Order By: Relevance
“…In the present study, the results showed that antimicrobial step-down therapy was associated with a significantly higher efficacy (85.29%) versus conventional antimicrobial therapy (61.29%), which was consistent with previous research results [ 18 , 19 ]. The efficacy of the convention antimicrobial therapy was lower than the results of prior research [ 20 ], which may be attributed to the limited number of study participants.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the results showed that antimicrobial step-down therapy was associated with a significantly higher efficacy (85.29%) versus conventional antimicrobial therapy (61.29%), which was consistent with previous research results [ 18 , 19 ]. The efficacy of the convention antimicrobial therapy was lower than the results of prior research [ 20 ], which may be attributed to the limited number of study participants.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, a randomized phase III trial was conducted in Korea comparing capecitabine monotherapy with CapeOX as standard therapy for rst-line treatment of metastatic GC patients over 70 years old. In the rst interim analysis, the median OS was better with CapeOX (11.1 months) than with single-agent capecitabine (6.3 months), although with no signi cant difference, and the independent data monitoring committee recommended discontinuation of the trial [32]. This trial was conducted in older patients with PS 0-2 and preserved organ function, suggesting that standard treatment is feasible and effective in this population.…”
Section: Discussionmentioning
confidence: 94%
“…[4][5][6] Fluoropyrimidine plus platinumbased chemotherapy has been widely used as first-line treatment for patients with advanced EC. 5,6 These systemic therapies rely primarily on cytotoxic chemotherapy, and the outcomes remain poor; however, emerging immunotherapy therapies (represented by cytotoxic T lymphocyte-associated antigen-4 [CTLA-4], programmed cell death protein 1 [PD-1], and programmed death ligand 1 [PD-L1] antibody drugs) have greatly improved treatment efficacies. [7][8][9][10][11] Immune checkpoint (IC) molecules are biological macromolecules expressed on human immune cells or other somatic cells that can regulate the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…EC patients in the early stage, often choose surgery; however, treatment options for metastatic EC are limited. First‐line chemotherapy treatment for metastatic patients is mainly based on fluorouracil or paclitaxel combined with platinum 4–6 . Fluoropyrimidine plus platinum‐based chemotherapy has been widely used as first‐line treatment for patients with advanced EC 5,6 .…”
Section: Introductionmentioning
confidence: 99%